2022
DOI: 10.3389/fpls.2022.986197
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic profiling of fresh and dried leaf extracts of young and mature Eucalyptus globulus trees indicates differences in the presence of specialized metabolites

Abstract: Aqueous extracts from Eucalyptus globulus leaves contain a wide variety of specialized metabolites, mainly polyphenols and appreciable amounts of volatile compounds, which are responsible for their diverse biological activities, such as antioxidant, antimicrobial, and allelopathic features. For this reason, several studies have been conducted to explore the composition of E. globulus leaf extracts for multiple therapeutic and commercial applications. However, so far, the available bibliographic reports only re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In comparison with other approaches, like AMP or other single-molecule therapies, the acquisition of bacterial resistance to plant extracts, as in the case of DLE, is less likely to occur, as they comprise a complex mixture of different compounds with distinct modes of action. In fact, as mentioned earlier, DLE is composed of many phenolic acids like gallic acid, galloylglucose digalloylglucose and the benzoic acid protocatechuic acid, which induce membrane disruption, organic acids such as arabinaric and tartaric acids, and flavonoids like quercetin [26]. Organic acids have the ability to cross membranes and can disrupt ATP production and induce cytoplasmic acidification [29], whereas flavonoids display multiple modes of action in bacterial cells, as they can inhibit biofilm formation, bacterial virulence, and nucleic acid, cell envelope, and peptidoglycan synthesis, besides disrupting membrane permeability [28].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In comparison with other approaches, like AMP or other single-molecule therapies, the acquisition of bacterial resistance to plant extracts, as in the case of DLE, is less likely to occur, as they comprise a complex mixture of different compounds with distinct modes of action. In fact, as mentioned earlier, DLE is composed of many phenolic acids like gallic acid, galloylglucose digalloylglucose and the benzoic acid protocatechuic acid, which induce membrane disruption, organic acids such as arabinaric and tartaric acids, and flavonoids like quercetin [26]. Organic acids have the ability to cross membranes and can disrupt ATP production and induce cytoplasmic acidification [29], whereas flavonoids display multiple modes of action in bacterial cells, as they can inhibit biofilm formation, bacterial virulence, and nucleic acid, cell envelope, and peptidoglycan synthesis, besides disrupting membrane permeability [28].…”
Section: Discussionmentioning
confidence: 89%
“…The growth of Pst, Xeu, and Cmm was differentially inhibited by DLE, resulting in distinct susceptibilities to the plant extract. A recent report from our group, which analysed the metabolomic profile of aqueous extracts of eucalyptus leaves, revealed that DLE-the one prepared with dried leaves of young E. globulus trees -, in comparison with those prepared with fresh leaves of juvenile and mature trees and dried leaf extracts of mature trees, presented appreciable amounts of phenolic acids, more specifically, gallic acid, digalloylglucose I, IV, and V, and galloylglucose I and II [26]. Due to their great affinity for lipids, phenolic acids, a class of specialized metabolites with notorious antibacterial properties, can easily cross membranes, causing cytoplasmic acidification and consequently inducing membrane disruption [32].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations